Adobe Dreamweaver CS6 revealed - Bishop, Sherry (Revealed series, 2013)
Discover all that Adobe® Dreamweaver® CS6 has to offer! Whether you're looking for a thorough introduction to Dreamweaver or a reliable reference for web design and development work, this proven resource is an ideal choice. ADOBE DREAMWEAVER CS6 REVEALED combines vibrant, full-color illustrations and clear, step-by-step tutorials to help readers master the industry-standard web development software. In addition to detailed information on the current Dreamweaver interface, features, and functionality, the text includes hands-on projects and real-world case studies to help readers hone their skills and appreciate their professional relevance. The text highlights features new to CS6 and explores cutting-edge web standards and design trends, including CSS3 best practices, HTML5 layouts, multiscreen preview, and media queries for mobile devices